Approximate Relationship for the Bond-Slip Using a Concrete Damage-Plastic Model - Ramin Tabatabaei Mirhosseini; Ehsan Araghizadeh; Soroush Rashidi (Advances in Materials Science and Engineering)
This paper presents an approximate multicontact model to study dynamic bond stress-slip based on the concrete damage-plastic model. To establish the bond stress-slip between rebar and concrete, an elastic-plastic steel cylinder contact element was used as the tube (ring contact element), and then, by reducing the bond strength, the amount of slip between rebar and concrete and its effect on concrete damage-plastic parameters were considered. When concrete cracks, the parameters of concrete cracking, the plasticity of rebar and concrete fracture, and the pull-out of rebar from concrete are used to consider the bond-slip relationship between rebar and concrete. Meanwhile, an external constraint in the cylinder model is taken into account. The bond strength calculated by the presented model is compared with the pull-out test specimen results, and the errors are generally within 15%. Finally, using the results obtained from the amount of slip in models, an approximate mathematical relationship between the slip of the rebar inside the concrete can be obtained in terms of the resistance of the ring contact element (instead of the concrete surrounding). This formula can be used to calculate the bond-slip rate of all the rebars of a structure. The results of the mentioned model using the ABAQUS software demonstrated that by reducing the strength of the ring contact element by 20%, slip increased by 4.2%. Also, with an 80% reduction in ring strength, the bond-slip rate increases by 45%. The proposed approximate relationship has reasonable accuracy and lower computational cost.